Influence of Magnesium Doping on the Photocatalytic and Antibacterial Properties of Hematite Nanostructures. Issue 3 (29th December 2021) - Joseph, Julie Ann; Nair, Sinitha B.; Mary, Surya A.; John, Sareen Sarah; Shaji, Sadasivan; Philip, Rachel Reena
Abstract : Herein, the effect of magnesium doping on hematite nanostructures prepared by a simple and cost‐effective electrochemical method is reported. Photocatalytic and antibacterial studies on the undoped and doped samples suggest improved performance for the Mg‐doped samples. Structural studies using X‐ray diffraction, Raman spectroscopy, and X‐ray photoelectron spectroscopy (XPS) in combination with field‐emission scanning electron microscopy for surface morphology confirm the Mg presence in the nanostructured hematite phase of iron oxide. Analyses of the valence band (VB) XPS spectra along with optical reflectance spectra indicate a shift in VB edge, characteristic of a conductivity type conversion from n‐type in hematite to p‐type in Mg‐doped hematite. The room temperature electrical conductivity is increased by three orders, and the optical bandgap is reduced by around 0.08 eV for moderately doped hematite nanostructures. Abstract : The preparation of Mg‐doped hematite nanostructures by an easy two‐stage anodization method is focused to achieve improved photocatalytic and antibacterial properties when compared with the undoped hematite. A shift in valence band edge is noticed with an increase in Mg doping concentration, leading to a conductivity type conversion from n‐ to p‐type.